Roles of Plasmalemma Aquaporin Gene StPIP1 in Enhancing Drought Tolerance in Potato - Wang, Li; Liu, Yuhui; Feng, Shoujiang; Yang, Jiangwei; Li, Dan; Zhang, Junlian (Frontiers in Plant Science, 2017)
Survival and mortality of plants in response to severe drought may be related to carbon starvation, but little is known about how plasma membrane intrinsic proteins may help alleviate the drought-induced consequence. Here, we determined the roles of plasmalemma aquaporin gene in improving plant water status, maintaining carbon accumulation, and thereby enhancing drought tolerance. Seven StPIP1 transformed potato (Solanum tuberosum L.) lines (namely T1, T2…T7) were compared with non-transgenic control plant at molecule and whole-plant levels. The relative expression of StPIP1 gene was found in leaves, stems and roots, with the most abundant expression being in the roots. The transgenic lines T6 and T7 had the highest StPIP1 expression, averaging 7.2 times that of the control and the greatest differences occurred 48 h after mannitol osmotic stress treatment. Using evaluation index to quantifying the degree of drought tolerance, we found the StPIP1 transgenic lines T6 and T7 had the highest drought tolerance, averaging 8.5 times that of the control. Measured at 30 days in drought stress treatment, the control plant decreased net photosynthetic rate by 33 and 56%, respectively, under moderate and severe stresses; also decreased stomatal conductance by 39 and 65%; and lowered transpiration rate by 49 and 69%, compared to the no-stress treatment, whereas the transgenic lines T6 and T7 maintained a relatively stable level with slight decreases in these properties. The constitutive overexpression of StPIP1 in potato improved plant water use efficiency and increased nonstructural carbohydrate concentration, which helped alleviate carbon starvation and minimized the loss of biomass and tuber yield due to drought stress. We conclude that the expression of StPIPs improves overall water relations in the plant and helps maintain photosynthesis and stomatal conductance; these help minimize carbon starvation and enhance the whole plant tolerance to drought stress.